2009
DOI: 10.1107/s0108270109046952
|View full text |Cite
|
Sign up to set email alerts
|

An unusual methylene aziridine refined inP21/cand the nonstandard settingP21/n

Abstract: The unusual methylene aziridine 6-tert-butyl-3-oxa-2-thia-1-azabicyclo[5.1.0]oct-6-ene 2,2-dioxide, C(9)H(15)NO(3)S, was found to crystallize with two molecules in the asymmetric unit. The structure was solved in both the approximately orthogonal and the oblique settings of space group No. 14, viz. P2(1)/n and P2(1)/c, respectively. A comparison of these results clearly displayed an increase in the correlation between coordinates in the ac plane for the oblique cell. The increase in the corresponding covarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Our re-refinement was performed with SHELXL (Sheldrick, 2008). The refined parameters obtained from SHELXL and from Feast et al (2009) were identical within standard uncertainties. The result of the P2 1 =n refinement is given in the left-hand column of Table 4 and of the P2 1 =c refinement in the right-hand column.…”
Section: Practical Application 1: Refinement In Different Space-groupmentioning
confidence: 90%
See 4 more Smart Citations
“…Our re-refinement was performed with SHELXL (Sheldrick, 2008). The refined parameters obtained from SHELXL and from Feast et al (2009) were identical within standard uncertainties. The result of the P2 1 =n refinement is given in the left-hand column of Table 4 and of the P2 1 =c refinement in the right-hand column.…”
Section: Practical Application 1: Refinement In Different Space-groupmentioning
confidence: 90%
“…It has been reported that refinement in oblique cells has increased correlation between selected parameters, potentially making the refinement unstable (Dunitz, 1995). The molecule methylene aziridine (Feast et al, 2009) can be described in space group P2 1 =n with cell parameters a = 13.8593 (3), b = 10.5242 (2), c = 14.8044 (4) Å , = 92.0014 (7) or space group P2 1 =c with cell parameters a = 13.8594 (2), b = 10.5243 (2), c = 19.9230 (3) Å , = 132.0439 (7) . In the oblique cell setting, Feast et al (2009) highlight an increase of the correlation between refined parameters.…”
Section: Practical Application 1: Refinement In Different Space-groupmentioning
confidence: 99%
See 3 more Smart Citations